Planck 2018 results: VI. Cosmological parameters (Corrigendum) - Aghanim, Nabila; Martinelli, Matteo (Astronomy and astrophysics, 2021)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics